Stereoselective chemo-enzymatic oxidation routes for (1R,3E,7E,11S,12S)-3,7,18-dolabellatriene - Görner, Christian; Hirte, Max; Huber, Stephanie; Schrepfer, Patrick; Brück, Thomas (Frontiers in Microbiology, 2015)
The diterpene (1R,3E,7E,11S,12S)-3,7,18-dolabellatriene from the marine brown alga Dilophus spiralis belongs to the dolabellanes natural product family and has antimicrobial activity against multi-drug resistant Staphylococcus aureus (MRSA). Recently, we generated a CotB2 diterpene synthase mutant (W288G), which instead of its native product cyclooctat-9-en-7-ol, generates (1R,3E,7E,11S,12S)-3,7,18-dolabellatriene. In vivo CotB2 W288G reconstitution in an E. coli based terpene production system, allowed efficient production of this olefinic macrocycle. To diversify the 3,7,18-dolabellatriene bioactivity we evaluated chemical and enzymatic methods for selective oxidation. Epoxidation by acetic peracid, which was formed in situ by a lipase catalyzed reaction of acetic acid with H2O2, provided efficient access to two monooxidized dolabellanes and to a novel di-epoxidated dolabellane species. These compounds could act as synthons en-route to new dolabellanes with diversified bioactivities. Furthermore, we demonstrate the almost quantitative 3,7,18-dolabellatriene conversion into the new, non-natural compound (1R,3E,7E,11S,12S,18R)-dolabella-3,7-diene-20-ol by hydroboration-oxidation with an enantiomeric excess of 94 %, for the first time.